The African challenge to global death penalty abolition: international human rights norms in local perspective - Novak, Andrew (Intersentia, 2016)
"Although the influence and opinions of political elites, civil society, and the general public vary widely, the death penalty is universally in decline throughout Sub-Saharan Africa. Today, the death penalty is a site of accommodation and resistance to international human rights norms between African governments and the Global North. As in debates over membership in the International Criminal Court and legal protections for sexual minorities, some leaders resist death penalty abolition as "imposed" by the Global North, though the modern death penalty in Africa is a product of European colonialism. However, Sub-Saharan Africa is not a passive subject of global death penalty abolition driven by Europe. Courts around the continent have made important contributions to global death penalty jurisprudence and members of civil society have engaged in novel and successful strategies against the death penalty. In addition, precolonial notions of punishment and criminal responsibility in Africa have influenced debates over the death penalty, including whether to provide compensation to victims of crime. This book explores the African contribution to te global death penalty debate and lessons for the international deat penalty abolition movement --Back cover